Governance and coordination in health care: organic processes and structural capacity. Issue 7 (3rd December 2019) - Nugus, Peter; Denis, Jean-Louis; Chênevert, Denis
Abstract : Purpose: The purpose of this paper is to articulate cutting-edge conceptions of the relationship between local processes in the here-and-now, and the broader influences on those processes, that are both organic and overtly designed, and to discern the implications of this relationship for future research, policy and practice. Design/methodology/approach: A focused and structured approach was taken to give effect to this purpose by reviewing the chosen articles in this collection, which from the 2018 Organizational Behavior in Health Care conference papers. Findings: Research in coordination within and across health care boundaries increasingly recognizes: the multilevel influences on human action and interaction in health care delivery; the challenge of balancing individual or local agency with overt interventions; the everchanging the local circumstances of healthcare delivery; and the need to foster reflexivity, that is, self-improvement capacity, in healthcare organizations. Research limitations/implications: Interventions to improve care coordination must be grounded in the reality of changing local circumstances and incentives for action from the broader environment. Originality/value: This paper articulates the implied tension in health care delivery between individual and local agency, and imposed structures that may contradict, but are at the same time necessary, to foster such agency.